Trends and Patterns of Burden of Disease and Injuries in Korea Using Disability-Adjusted Life Years - Kim, Young-Eun (J Korean Med Sci, 2019)
BACKGROUND: It is extremely important to objectively take a view of population health to provide useful information to decision makers, health-sector leaders, researchers, and informed citizens. This study aims to examine the burden of disease in Korea as of 2015, and to study how the burden of disease changes with the passage of time. METHODS: We used results from the Korean National Burden of Disease and Injuries Study 2015 for all-cause mortality, cause-specific mortality, and non-fatal disease burden to derive disability-adjusted life years (DALYs) by gender and age groups from 2007 to 2015. DALYs were calculated as the sum of the years of life lost (YLLs) and the years lived with disability (YLDs). RESULTS: In 2015, the burden of disease for Korean people was calculated at 29,476 DALYs per 100,000 population. DALYs caused by low back pain were the highest, followed by diabetes mellitus and chronic obstructive pulmonary disease. The burden of disease showed a consistently increasing trend from 2007 to 2015. Although YLLs have been on the decrease since 2011, the increase in YLDs has contributed to the overall rise in DALYs. The DALYs per 100,000 population in 2015 increased by 28.1% compared to 2007. CONCLUSION: As for the diseases for which the burden of disease is substantially increasing, it is needed to establish appropriate policies in a timely manner. The results of this study are expected to be the basis for prioritizing public health and health care policies in Korea.